Meningkatkan Pengelolaan Manajemen Keuangan Sekolah Melalui Metode Transparansi Berdasarkan Konstruksi Pendidikan Kristen - Rifka Siva Br Sinaga; Ratu Pranatalia; Suardin Zai (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
It was found that there were still many irregularities in school financial management which resulted in the school financial system being unsystematic. The aim of this research is to find out how the school financial transparency system works to create a smart school with a management system with good integrity based on the construction of Christian education. The research method used in this research uses descriptive qualitative research methods. The results show that if financial transparency can be implemented well, many parties will benefit and schools will gain good accountability. It is hoped that with this research, more schools will be able to implement school financial transparency.